2023
DOI: 10.1002/inf2.12400
|View full text |Cite
|
Sign up to set email alerts
|

Carrier recombination suppression and transport enhancement enable high‐performance self‐powered broadband Sb2Se3 photodetectors

Abstract: Antimony selenide (Sb2Se3) is a promising candidate for photodetector applications boasting unique material benefits and remarkable optoelectronic properties. Achieving high‐performance self‐powered Sb2Se3 photodetector through a synergistic regulation of absorber layer and heterojunction interface demonstrates great potential and needs essential investigation. In this study, an effective two‐step thermodynamic/kinetic deposition technique containing sputtered and selenized Sb precursor is implemented to induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 52 publications
0
49
0
Order By: Relevance
“…[ 46 ] According to a previous report, it is favorable for simultaneously suppressing carrier recombination at interface and enhancing the carrier transfer across the interface. [ 47 ] In addition, the split of quasi‐Fermi levels including the hole quasi‐Fermi level ( E qFp ) and the electron quasi‐Fermi level ( E qFn ) under illumination are also portrayed in Figure 5e; the ideal photovoltage ( V ph ) determines the maximum onset potential ( V on ). Afterward, to gain a deeper insight of the nature of this CZTSSe/CdS heterojunction interface and its effect on photoelectric device performance, the corresponding photovoltaic devices with similar device configuration (i.e., Mo/CZTSSe/CdS/ITO/Ag) were fabricated, and labeled as PV‐1, PV‐2, and PV‐3, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[ 46 ] According to a previous report, it is favorable for simultaneously suppressing carrier recombination at interface and enhancing the carrier transfer across the interface. [ 47 ] In addition, the split of quasi‐Fermi levels including the hole quasi‐Fermi level ( E qFp ) and the electron quasi‐Fermi level ( E qFn ) under illumination are also portrayed in Figure 5e; the ideal photovoltage ( V ph ) determines the maximum onset potential ( V on ). Afterward, to gain a deeper insight of the nature of this CZTSSe/CdS heterojunction interface and its effect on photoelectric device performance, the corresponding photovoltaic devices with similar device configuration (i.e., Mo/CZTSSe/CdS/ITO/Ag) were fabricated, and labeled as PV‐1, PV‐2, and PV‐3, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The prepared Cd­(Se,Te) thin films present excellent material properties in terms of their morphology and optical absorption. The defects and carrier lifetime also play significant roles in the performance of CdSe optoelectronic devices . Previous experiments have shown that the average carrier lifetime of the CdSe thin film is less than 200 ps, which is the most important factor greatly limiting the efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…The defects and carrier lifetime also play significant roles in the performance of CdSe optoelectronic devices. 31 Previous experiments have shown that the average carrier lifetime of the CdSe thin film is less than 200 ps, which is the most important factor greatly limiting the efficiency. As the DFT calculation mentioned above, the Te element serves as a good passivation for the CdSe thin films that can reduce the hole capture coefficient and the recombination rate, hence it is theoretically possible to increase the carrier lifetime.…”
Section: Resultsmentioning
confidence: 99%
“…The similar phenomenon has also been observed in other 1D crystal-structural materials, such as Sb 2 Se 3 and Sb 2 S 3 . [67][68][69][70][71][72][73][74] When the post-annealing temperature increases beyond 260 °C, the grains start to grow fast and become rounded (Figure 2e-h), attributed to the intensive fusion of Te and Se atoms in the film. However, when the annealing temperature comes over 300 °C, the excessive annealing temperatures would increase atomic fluidity and destroy the crystal structure.…”
Section: Materials Properties Of Te 07 Se 03 Filmsmentioning
confidence: 99%